PENYEDIAAN FASILITAS PENDUKUNG UNTUK MENINGKATKAN PEMBELAJARAN BAGI SISWA BERKEBUTUHAN KHUSUS DI SEKOLAH UMUM - Megawati, Megawati; Lutfiani, Dhea; Andriani, Opi (Jurnal Pendidikan Vokasi dan Seni, 2023)
The purpose of this research is to determine the educational facilities at SDN 036/II Sarana Jaya. to improve learning for students with special needs. This research uses a qualitative descriptive method with interviews and documentation. The research subjects are Mrs. Reni Maryani as the class teacher at SDN 036/II Saran Jaya and the 5th grade students at SDN 036/II Sarana Jaya. Meanwhile, the research object is the implementation of the learning process at SDN 036/II Saran Jaya. From this research, it was concluded that at SDN 036/II Sarana Jaya, children with special needs (speech impaired) in Bungo Regency received facilities according to their needs, namely in the form of communication boards that made it easier for the children to express what they wanted to convey.